A study on the factors that influence gold price in Malaysia / Mohd Kamarulredzal Kamarulzaman - Kamarulzaman, Mohd Kamarulredzal (2013)
There are many factors that affect gold price in Malaysia. The objective of this study is to observe the factors that affect the movement of gold price in Malaysia for investment purposes. As to conduct this study, the data will be collected from historical return among variables by using the time series data starting from 2006 to 2013 using quarterly basis. The implication of this study is to analyze whether each of the variables may directly affect the gold price fluctuation. This research used Multiple Regression. The dependent variable will be the gold price which is measured by gold prices while the independent variables will be the inflation rate, exchange rate, stock market volatility and gross domestic product. The result of this research is significant for inflation rate, exchange rate and gross domestic product but not significant for stock market index